Strong versus weak sustainable development in the blue economy: a study of 15 EU coastal countries - Christoph Spenger; Ignacio Saldivia Gonzatti; Lennard Kröger; Christopher Robin Fleet; Rudi Voss; Wilfried Rickels (npj Ocean Sustainability, 2024)
One of the European Union's environmental and sustainable development objectives is to achieve sustainable marine development, combining the objectives of ocean health and the blue economy. Developing, implementing, and monitoring marine policies requires information on the status and evolution of marine development at the country level, including the extent to which strong sustainable development (i.e., balanced development across socio-economic and environmental dimensions) is being achieved. Here, we provide a comprehensive assessment of progress towards marine development for 15 European Union coastal countries in the Baltic, North, and Atlantic Seas, covering the period 2012–2022 and using information from Sustainable Development Goal 14 to derive our indicator framework. We show that the EU is achieving sustainable marine development, but not comprehensively in all countries. While seven countries achieved sustainable development under both weak and strong sustainability, seven countries developed only under weak sustainability, and one country made no progress under either concept.
Keywords: 330